2018
DOI: 10.5114/aoms.2015.55203
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and clinical aspects of the occurrence of accessory (multiple) renal arteries

Abstract: Renal vascularization variants vastly differ between individuals due to the very complex embryogenesis of the kidneys. Moreover, each variant may have implications for clinical and surgical interventions. The number of operating procedures continues to grow, and includes renal transplants, aneurysmorrhaphy and other vascular reconstructions. In any surgical technique, unawareness of the presence of multiple renal arteries may result in a fatal outcome, especially if laparoscopic methods are used. The aim of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 69 publications
1
46
0
Order By: Relevance
“…We did not find a statistically significant relationship between the prevalence of extra renal arteries and the location of the horseshoe kidney in relation to the midline, which stays in opposition to the results published by Taghavi et al [ 38 ]. Available data on the prevalence of right- and left-sided extra renal arteries in individuals with separated kidneys are inconclusive, and likewise in the case of horseshoe kidneys, those vessels are not always observed and their presence seems to be population-specific [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…We did not find a statistically significant relationship between the prevalence of extra renal arteries and the location of the horseshoe kidney in relation to the midline, which stays in opposition to the results published by Taghavi et al [ 38 ]. Available data on the prevalence of right- and left-sided extra renal arteries in individuals with separated kidneys are inconclusive, and likewise in the case of horseshoe kidneys, those vessels are not always observed and their presence seems to be population-specific [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…55 The most popular visualizing techniques of vessels include angiography, computed tomography, ultrasonography, magnetic resonance, and their modifications. While many studies are based on dissected cadavers or specimens from the autopsy, other angiographic studies are based on living patients.…”
Section: Visualising Techniquementioning
confidence: 99%
“…29 Literature review showed that variation in the incidence of presence of ARA in different studies was probably due to a complex embryogenesis of kidneys and renal vasculature. 12,30 In our study among different types of accessory renal arteries we found most frequent superior polar artery 14.9% (n=37), then hilar artery was 10.2% (n=26) and lowest frequency of inferior polar artery 1.3% (n= 3). A study conducted in India reported highest incidence of hilar accessory artery 22.6 %, than superior polar artery was 13.1 % and lowest incidence of inferior polar artery 7.1%.…”
Section: Discussionmentioning
confidence: 54%
“…Extra renal arteries are vestigial structures that develop due to failure to degenerate, during ascent of primordial permanent kidney (metanephros). 12 In developing human embryo, permanent kidney which is metanephros ascends from pelvic cavity to abdomen. During its ascent it receives blood vessels close to it.…”
Section: Introductionmentioning
confidence: 99%